Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let's begin by matching each quadratic equation with its solution set.
We use the provided solutions:
1. [tex]\(2x^2 - 8x + 5 = 0\)[/tex]
- Solution: [tex]\[ [2 - \frac{\sqrt{6}}{2}, 2 + \frac{\sqrt{6}}{2}] \][/tex]
2. [tex]\(2x^2 - 10x - 3 = 0\)[/tex]
- Solution: [tex]\[ [\frac{5}{2} - \frac{\sqrt{31}}{2}, \frac{5}{2} + \frac{\sqrt{31}}{2}] \][/tex]
3. [tex]\(2x^2 - 8x - 3 = 0\)[/tex]
- Solution: [tex]\[ [2 - \frac{\sqrt{22}}{2}, 2 + \frac{\sqrt{22}}{2}] \][/tex]
4. [tex]\(2x^2 - 9x - 1 = 0\)[/tex]
- Solution: [tex]\[ [\frac{9}{4} - \frac{\sqrt{89}}{4}, \frac{9}{4} + \frac{\sqrt{89}}{4}] \][/tex]
5. [tex]\(2x^2 - 9x + 6 = 0\)[/tex]
- Solution: [tex]\[ [\frac{9}{4} - \frac{\sqrt{33}}{4}, \frac{9}{4} + \frac{\sqrt{33}}{4}] \][/tex]
Now let's identify the expressions provided:
- [tex]\(\frac{2 \pm \sqrt{80}}{4}\)[/tex]
- Simplification: [tex]\(\frac{2 \pm \sqrt{80}}{4} = \frac{2 \pm \sqrt{4 \cdot 20}}{4} = \frac{2 \pm 2\sqrt{20}}{4} = \frac{2 \pm 2\sqrt{2 \cdot 10}}{4} = \frac{2 \pm 2\sqrt{10}}{4} = \frac{1 \pm \sqrt{10}}{2}\)[/tex]
- None of the equations match with this solution set.
- [tex]\(\frac{4 \pm \sqrt{22}}{2}\)[/tex]
- Simplification: [tex]\(\frac{4 \pm \sqrt{22}}{2} = 2 \pm \frac{\sqrt{22}}{2}\)[/tex]
- This matches with the equation [tex]\(2x^2 - 8x - 3 = 0\)[/tex].
Hence, the correct matches are:
[tex]\[ \begin{array}{l} \frac{2 \pm \sqrt{80}}{4} \longrightarrow \text{None of the provided equations} \\ \frac{4 \pm \sqrt{22}}{2} \longrightarrow 2x^2 - 8x - 3 = 0 \\ \end{array} \][/tex]
We use the provided solutions:
1. [tex]\(2x^2 - 8x + 5 = 0\)[/tex]
- Solution: [tex]\[ [2 - \frac{\sqrt{6}}{2}, 2 + \frac{\sqrt{6}}{2}] \][/tex]
2. [tex]\(2x^2 - 10x - 3 = 0\)[/tex]
- Solution: [tex]\[ [\frac{5}{2} - \frac{\sqrt{31}}{2}, \frac{5}{2} + \frac{\sqrt{31}}{2}] \][/tex]
3. [tex]\(2x^2 - 8x - 3 = 0\)[/tex]
- Solution: [tex]\[ [2 - \frac{\sqrt{22}}{2}, 2 + \frac{\sqrt{22}}{2}] \][/tex]
4. [tex]\(2x^2 - 9x - 1 = 0\)[/tex]
- Solution: [tex]\[ [\frac{9}{4} - \frac{\sqrt{89}}{4}, \frac{9}{4} + \frac{\sqrt{89}}{4}] \][/tex]
5. [tex]\(2x^2 - 9x + 6 = 0\)[/tex]
- Solution: [tex]\[ [\frac{9}{4} - \frac{\sqrt{33}}{4}, \frac{9}{4} + \frac{\sqrt{33}}{4}] \][/tex]
Now let's identify the expressions provided:
- [tex]\(\frac{2 \pm \sqrt{80}}{4}\)[/tex]
- Simplification: [tex]\(\frac{2 \pm \sqrt{80}}{4} = \frac{2 \pm \sqrt{4 \cdot 20}}{4} = \frac{2 \pm 2\sqrt{20}}{4} = \frac{2 \pm 2\sqrt{2 \cdot 10}}{4} = \frac{2 \pm 2\sqrt{10}}{4} = \frac{1 \pm \sqrt{10}}{2}\)[/tex]
- None of the equations match with this solution set.
- [tex]\(\frac{4 \pm \sqrt{22}}{2}\)[/tex]
- Simplification: [tex]\(\frac{4 \pm \sqrt{22}}{2} = 2 \pm \frac{\sqrt{22}}{2}\)[/tex]
- This matches with the equation [tex]\(2x^2 - 8x - 3 = 0\)[/tex].
Hence, the correct matches are:
[tex]\[ \begin{array}{l} \frac{2 \pm \sqrt{80}}{4} \longrightarrow \text{None of the provided equations} \\ \frac{4 \pm \sqrt{22}}{2} \longrightarrow 2x^2 - 8x - 3 = 0 \\ \end{array} \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.